Effect of partial root-zone drying irrigation timing on potato tuber yield and water use efficiency - Yactayo, Wendy; Ramírez, David A.; Gutiérrez, Raymundo; Mares, Víctor; Posadas, Adolfo; Quiroz, Roberto (Elsevier, 2013)
Partial root-zone drying (PRD) is an irrigation technique which has shown increased water use efficiency (WUE) without yield reductions in potato and other crops. However, questions remain as to the effect of the water restriction initiation timing and the level of alternate water restriction on the response of the potato crop. In this study, we tested: two PRD treatments with 25% (PRD25) and 50% (PRD50) of total water used in full irrigation (FI, as control), and a deficit irrigation treatment with 50% of water restriction (DI50). Two water restriction initiation timings were tested at: 6 weeks (WRIT6w) and 8 weeks (WRIT8w) after planting. Osmotic potential ( ), osmotic adjustment, relative water content and chlorophyll concentration were assessed in four dates during the growing period. PRD50 initiated at WRIT6w showed the highest WUE without a tuber yield reduction respect to the control. While plants under PRDs and DI50 showed lower than FI, PRDs treatments promoted higher osmotic adjustment particularly in WRIT6w. Our study suggests that early PRDs with mild water restriction allow drought hardiness (improving water stress response) and water saving avoiding a dramatic yield tuber reduction.